Neighbourhood interactions drive overyielding in mixed-species tree communities - Andreas Fichtner (Nature Portfolio, 2018)
Though biodiversity is expected to be important in productivity in tree communities, there is little empirical evidence of this at local scales. Here, Fichtner et al. show that higher neighbourhood species richness increased tree growth, explaining over half of the variation in community productivity.